2016
DOI: 10.1038/srep26199
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex class I proteins are critical for maintaining neuronal structural complexity in the aging brain

Abstract: Major histocompatibility complex class I (MHCI) proteins have been implicated in neuronal function through the modulation of neuritogenesis, synaptogenesis, synaptic plasticity, and memory consolidation during development. However, the involvement of MHCI in the aged brain is unclear. Here we demonstrate that MHCI deficiency results in significant dendritic atrophy along with an increase in thin dendritic spines and a reduction in stubby spines in the hippocampus of aged (12 month old) mice. Ultrastructural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 53 publications
5
67
1
Order By: Relevance
“…This result suggests that β2M is closely related to central nervous system inflammation. Recently, the impact of MHC I of the development of the nervous system has attracted researchers' attention, as MHC I plays an important role in regulating axon growth and cortical connections (36). Furthermore, TNF-α and γ-interferon can promote the expression of MHC I and β2M in the central nervous system (37).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that β2M is closely related to central nervous system inflammation. Recently, the impact of MHC I of the development of the nervous system has attracted researchers' attention, as MHC I plays an important role in regulating axon growth and cortical connections (36). Furthermore, TNF-α and γ-interferon can promote the expression of MHC I and β2M in the central nervous system (37).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MHCI is essential for N‐methyl‐ d ‐aspartic acid (NMDA) receptor‐ and hippocampus‐dependent memory, and MHCI KO (β2m–/– TAP–/–) mice show dysfunctions in social interaction and object recognition (Nelson et al, ). The genetic manipulation of MHCI molecules leads to changes in α‐amino‐2,3‐dihydro‐5‐methyl‐3‐oxo‐4‐isoxazolepropanoic acid and NMDA receptor expression, resulting in impairments in learning and memory (Fourgeaud et al, ; Lazarczyk et al, ). In addition, MHCI negatively regulates the cortical excitation and inhibition balance (Elmer et al, ; Glynn et al, ; Washburn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, immune-related receptors such as MHC-I, TNFR1, and IL-1R participate in LTP and modulate learning and memory formation [ 114 ]. For example, neurons from MHC-I-knockout mice show increased synaptic plasticity, excitability, and LTP [ 138 ], which is increased in 12-month old mice [ 139 ], likely exerting this effect via modification of NMDAR and α-amino-3hydorxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) function and trafficking [ 140 ]. It has recently been shown that IL-1β directly suppresses hippocampal plasticity via neuron-specific mechanisms [ 141 ] and that increased pro-inflammatory IL-1 accessory protein signaling, specifically at the synapse, underlies the augmented vulnerability to IL-1β-mediated cognitive impairment that occurs with age [ 142 ].…”
Section: Chronic Inflammation Impairs Cognition and Synaptic Plasticimentioning
confidence: 99%